Patterns of International Capital Raisings - Gozzi, Juan Carlos; Levine, Ross; Schmukler, Sergio L. (2012)
This paper documents several new patterns associated with firms issuing stocks and bonds in foreign markets that motivate the need for and help guide the direction of future research. Three major patterns stand out. (1) A large and growing fraction of capital raisings, especially debt issuances, occurs in international markets, but a very small number of firms accounts for the bulk of international capital raisings, highlighting the cross-firm heterogeneity in financial globalization. (2) Changes in firm performance following equity and debt issuances in international markets are qualitatively similar to those following domestic issuances, suggesting that capital raisings abroad are not intrinsically different from those in domestic markets. (3) Firms continue to issue securities both abroad and at home after accessing international markets, suggesting that international and domestic markets are complements, not substitutes. Existing theories do not fully account for these patterns.